Pengaruh Ukuran Perusahaan, Reputasi Auditor, Profitabilitas, dan Solvabilitas Terhadap Audit Delay(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Chasanah, Uswatun, Dra. Rina Trisnawati, Ak, M.si, Ph.D (2016)
The purpose of this research is to examine the signifacation impact of firm size, reputation of public accountant, profitability and solvability toward audit delay. The population of this research is manufacturing companies listed in Indonesia Stock Exchange. Sampling technique that used in this study is the purposive sampling. The method of analysis used to test the hypothesis is multiple linear regression analysis. The sample used in this study are 28 companies during 2012-2014. The Results of this research show thatfirm size and profitability have no significant effect on audit delay, meanwhile reputation of public accountant and solvability have significant effect on audit delay.